МОДЕЛЬ РЕЗОНАНСНОГО ТРАНЗИСТОРНОГО ІНВЕРТОРА НАПРУГИ З НИЗЬКОЧАСТОТНОЮ ІМПУЛЬСНОЮ МОДУЛЯЦІЄЮ - Юрченко, О.М.; Гуцалюк, В.Я.; Герасименко, П.Ю.; Слєсаревський, І.О. (Інститут електродинаміки НАН України, Київ, 2010)
Transistor inverters are widely used in induction heating systems with the frequency range of 10-440 kHz. The inverter circuit which consists of noncontrolled rectifier and control voltage inverter finds its application for realization of majority technological tasks. In the article it is considered the bridge-type voltage inverter circuit to the output of which it is connected the inductor with heated body and balancing capacitor through the matching transformer. The inverter load substitution circuit can be represented as series-resonant circuit which consists of the inductance L, capacity C and active resistance R. Light dynamic power loss is the great advantage of inverters with low frequency (LF) regulation in comparison with the control method on the fundamental frequency. It can be obtained by transistors' switching at the approximate to zero current which corresponds to the operation mode at the frequency approximate to the frequency of resonant circuit. To provide it the system of automatic frequency tuning is used. By LF modulation it is rational to define the time of modulation Tm and ontime t on or offtime t off as integer numbers which are multiple of inverter output voltage period where n is a number of inverter output voltage periods during t off ; m is a number of inverter output voltage periods during t on ; s is a number of inverter output voltage periods T 0 during Tm. Mathematical model of transistor voltage inverter with the output series-resonant circuit in the form of two systems of equations describing instantaneous current on the inverter's output and the resonant capacitor voltage for two intervals t on and t off has been worked out. Worked out mathematical model allows to perform the operation analysis of transistor voltage inverter with LF pulse modulation at different combinations n, m, s. In order to verify the validation of tolerance concerning the analysis by first harmonic and findings accuracy, computer simulation of the operation of series-resonant transistor voltage inverter with LF pulse modulation at LF-PDM and LF-PFM (n=1 & n=2) was performed. Dependence of mathematical model maximum error ???? on resonant-circuit Q-factor was obtained. References 6, figures 4.